A dead hand eaudiobook A crime in calcutta. - Theroux, Paul (Recorded Books Inc., 2010)
Best-selling author Paul Theroux has been hailed as a "masterful and mesmerizing storyteller" (Booklist). Theroux's A Dead Hand unfolds around Jerry Delfont, a travel writer living in Calcutta and suffering from writer's block. But when Jerry receives a letter from a wealthy fan requesting help, he soon finds himself entangled in a mystery involving a dead boy and an innocent man fleeing for his life.